2023
DOI: 10.1021/jacsau.3c00041
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium- and Alkyne-Based Bioorthogonal Raman Probes for In Situ Quantitative Metabolic Imaging of Lipids within Plants

Abstract: Plants can rapidly respond to different stresses by activating multiple signaling and defense pathways. The ability to directly visualize and quantify these pathways in real time using bioorthogonal probes would have practical applications, including characterizing plant responses to both abiotic and biotic stress. Fluorescence-based labels are widely used for tagging of small biomolecules but are relatively bulky and with potential effects on their endogenous localization and metabolism. This work describes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…(2) Wei and co-workers 137 demonstrated a hydrogen− deuterium exchange (HDX) strategy to sense local chemical and environment changes in cells (e.g., acidity) using terminal alkyne-tagged Raman probes, which is based on the idea that deuteration of the alkynyl hydrogen can cause a large red shift in its Raman peak (>100 cm −1 in their cases); in addition, they reported a strategy to generate alkyne Raman probes via photoinduced cyclopropenone caging, allowing them to perform multicolor live-cell SRS imaging and tracking; 150 (3) Numata and co-workers 151 demonstrated that terminal alkynebased Raman probes that mimic choline and octadecanoic acid can be used to track and quantify such metabolite's uptake and the corresponding metabolic pathways within intact Arabidopsis thaliana (A. thaliana) roots and tobacco Bright Yellow-2 (BY-2) culture cells; (4) Liu and co-workers 152 developed a urinary biomarker, which consists of two alkyne-containing moieties with one behaving as an internal standard and one acting as a disease responsive unit, for quantitatively monitoring cancer development in real time via surface enhanced Raman spectroscopy; and (5) Londergan and coworkers 153 demonstrated that the Raman signals arising from both aliphatic and aromatic terminal alkynes show strong solvatochroism and, hence, can be used to report local electronic interactions in proteins (i.e., via a genetically incorporable alkyne-containing nonnatural amino acid, such as p-ethynylphenylalanine). Furthermore, various strategies have been developed to increase the Raman scattering cross section of alkynes used in biological studies or expand their utilities.…”
Section: In Biological Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…(2) Wei and co-workers 137 demonstrated a hydrogen− deuterium exchange (HDX) strategy to sense local chemical and environment changes in cells (e.g., acidity) using terminal alkyne-tagged Raman probes, which is based on the idea that deuteration of the alkynyl hydrogen can cause a large red shift in its Raman peak (>100 cm −1 in their cases); in addition, they reported a strategy to generate alkyne Raman probes via photoinduced cyclopropenone caging, allowing them to perform multicolor live-cell SRS imaging and tracking; 150 (3) Numata and co-workers 151 demonstrated that terminal alkynebased Raman probes that mimic choline and octadecanoic acid can be used to track and quantify such metabolite's uptake and the corresponding metabolic pathways within intact Arabidopsis thaliana (A. thaliana) roots and tobacco Bright Yellow-2 (BY-2) culture cells; (4) Liu and co-workers 152 developed a urinary biomarker, which consists of two alkyne-containing moieties with one behaving as an internal standard and one acting as a disease responsive unit, for quantitatively monitoring cancer development in real time via surface enhanced Raman spectroscopy; and (5) Londergan and coworkers 153 demonstrated that the Raman signals arising from both aliphatic and aromatic terminal alkynes show strong solvatochroism and, hence, can be used to report local electronic interactions in proteins (i.e., via a genetically incorporable alkyne-containing nonnatural amino acid, such as p-ethynylphenylalanine). Furthermore, various strategies have been developed to increase the Raman scattering cross section of alkynes used in biological studies or expand their utilities.…”
Section: In Biological Sciencementioning
confidence: 99%
“…For example, they have been used to image and interrogate a wide variety of biological molecules, such as proteins, nucleic acids, glycans, and small metabolites, in live cells via stimulated Raman scattering (SRS) microscopy. Since this topic has been extensively reviewed, ,, below we only briefly discuss several recent studies in this area, highlighting the increased utility of the CC stretching vibration in biological science. For example, (1) Min and co-workers developed a new set of ultrabright and compact Raman-active nanoparticles (Rdots) that are composed of polyyne-based dyes (or other alkyne-containing molecules) and further demonstrated that, when used in conjunction with SRS microscopy, such Rdots can lead to a detection limit down to pM scale in solution and even allow single-particle imaging; (2) Wei and co-workers demonstrated a hydrogen–deuterium exchange (HDX) strategy to sense local chemical and environment changes in cells (e.g., acidity) using terminal alkyne-tagged Raman probes, which is based on the idea that deuteration of the alkynyl hydrogen can cause a large red shift in its Raman peak (>100 cm –1 in their cases); in addition, they reported a strategy to generate alkyne Raman probes via photoinduced cyclopropenone caging, allowing them to perform multicolor live-cell SRS imaging and tracking; (3) Numata and co-workers demonstrated that terminal alkyne-based Raman probes that mimic choline and octadecanoic acid can be used to track and quantify such metabolite’s uptake and the corresponding metabolic pathways within intact Arabidopsis thaliana ( A. thaliana ) roots and tobacco Bright Yellow-2 (BY-2) culture cells; (4) Liu and co-workers developed a urinary biomarker, which consists of two alkyne-containing moieties with one behaving as an internal standard and one acting as a disease responsive unit, for quantitatively monitoring cancer development in real time via surface enhanced Raman spectroscopy; and (5) Londergan and co-workers demonstrated that the Raman signals arising from both aliphatic and aromatic terminal alkynes show strong solvatochroism and, hence, can be used to report local electronic interactions in proteins (i.e., via a genetically incorporable alkyne-containing nonnatural amino acid, such as p -ethynylphenylalanine).…”
Section: Application Of Cc Stretching Vibration In Biological Sciencementioning
confidence: 99%
“…Nonetheless, this versatile technique has already found abundant new opportunities for analyzing a wide range of metabolites (e.g., amino acids, fatty acids, nucleic acids, glucose, cholesterol, choline, glycogen, etc.) and uncovered many previously unknown regulatory and disease-related roles spanning from cell biology , and cancer biology to neuroscience, microbiology, and even plant biology (Figure c–f, Table S1). By utilizing endogenous vibrational signatures or coupling with minimally perturbative and bioorthogonal vibrational probes including alkynes and isotopes, SRS can function as both an untargeted (unlabeled) and a targeted (labeled) approach.…”
Section: Introductionmentioning
confidence: 99%